The role of stents in the treatment of Crohn’s disease strictures - Loras Alastruey, Carme; Andújar Murcia, Xavier; Esteve Comas, Maria (Endoscopy International Open, 2016)
Background and aims: Stenosis is one of the most frequent local complications in Crohn’s disease (CD). Surgery is not the ideal treatment because of the high rate of postoperative recurrence. Endoscopic balloon dilation (EBD) currently is the current treatment of choice for short strictures amenable to the procedure. However, it is not applicable or effective in all the cases, and it is not without related complications. Our goal was to summarize the published information regarding the use and the role of the stents in the treatment of CD stricture. A Medline search was performed on the terms “stricture,” “stenosis,” “stent” and “Crohn’s disease.” Results: a total of 19 publications met our search criteria for an overall number of 65 patients. Placing a self-expanding metal stent (SEMS) may be a safe and effective alternative to EBD and/or surgical intervention in the treatment of short stenosis in patients with CD. Indications are the same as those for EBD. In addition, SEMS may be useful in stenosis refractory to EBD and may be suitable in the treatment of longer or more complex strictures that cannot be treated by EBD. With the current information, it seems that the best treatment option is the placement of a fully covered stent for a mean time of 4 weeks. Regarding the use of biodegradable stents, the information is limited and showing poor results. Conclusions: the use of stents in the treatment of strictures in CD should be taken into account either as a first endoscopic therapy or in case of EBD failure.